#TITLE_ALTERNATIVE# - C. Sitompul (NIM 132 03 64) , Amry
Abstract: Power control in code division multiple access (CDMA) system is a mechanism aimed to control the transmit power of both mobile station (MS) and base station (BS). On the uplink channel, closed-loop power control is focused to mitigate the signal fluctuation due to the multipath fading channel behaviour, and as to minimize the interuser interference. In signal to interference ratio (SIR)-based closed-loop power control scheme, the accuracy of estimated SIR value is critically needed since it will be employed by BS to determine the update power level of MS. The final project will evaluate the impact of SIR estimation error as a result of imperfect SIR estimator. This study will be performed by computer simulation using MATLAB. The estimation error impacts that will be considered are power control error level which is the difference between the achieved SIR from its target SIR level, and also the system performance evaluated by using bit error rate (BER) parameter. The simulation results show that SIR estimation error can increase the PCE, with a bigger increment on variabel step-size compared to the fixed-step algorithm. Estimation error also cause false power control command occurrence, and later decrease the systems BER performance. The fixed-step size algorithm is more robust to estimation error effect than the variable-step size